Disability in Daily Living Activities, Family Dysfunction, and Late-Life Suicide in Rural China: A Case–Control Psychological Autopsy Study - Cao, Rifang; Jia, Cunxian; Ma, Zhenyu; Niu, Lu; Zhou, Liang (Frontiers in Psychiatry, 2019)
Background: Although late-life suicide in rural China is a matter of concern, research is scarce addressing the association between capability of daily living activities, family function, and late-life suicide. We conducted this psychological autopsy study to explore associations between disability in daily living activities, family dysfunction, and late-life suicide in rural China. Methods: Using a 1:1 matched case-control design, we collected data from 242 elderly suicide cases and 242 living community controls in rural China using the psychological autopsy method. We used Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders (SCID), Activities of Daily Living Scale (ADL), and Family Adaptive, Partnership, Growth, Affection and Resolve scale (APGAR) to assess the presence of mental disorders, capability of daily living activities, and family function, respectively. Results: Compared with the living controls, suicide cases presented more severe impairment in capability of daily living activities and poorer family function. After controlling for all other factors, capability of daily living activities and family function remained in the final model. The results of the multivariate analysis also show that the presence of a mental disorder, lower levels of social support, and increased number of life events in the last year were significantly associated with elevated suicide risk. Conclusions: Disability in daily living activities and family dysfunction are associated with elevated risk of late-life suicide in rural China. It is warranted to design programs, including family interventions, peer-support groups, and community programs, to help the rural elderly improve activities of daily living and obtain the social support they need to prevent suicidal behaviors.